A Study on Characteristics of Small-Scale Plastic Industries in Dhaka North and South City Corporations - Majumder, Tasnim Anika; Nur, S M Shihab; Haque, Afsana (Journal of Bangladesh Institute of Planners, 2018)
Small scale plastic industries have become an important sector in Bangladesh as it covers a significant portion of the informal economy. The study aims at identifying the characteristics of these industries which makes the condition more vulnerable. In this research, both qualitative and quantitative data have been collected through questionnaire and observation surveys. For identifying the characteristics of industries, owners and workers of 240 industries have been surveyed. The study reveals that most of these industries are concentrated in Old Dhaka due to raw materials and labor availability and market proximity. In most of the cases, the land uses of these industries are incompatible as around 57% of these industries are developed in mixed use areas or more specifically in the residential neighborhood. There are mainly two types of machines used in these industries, of which the local ‘Dana machine’ creates more environmental pollution. Though these industries provide various types of products, it also has left a negative impact on our daily life and environment as well. At the same time, the existing procedure of utilizing the waste to produce new goods cannot also get rid of the contribution to environmental pollution. As most of these industries have low capital investment and have established in congested residential areas, it is quite impossible for these industries to reduce environmental pollution by providing ETP and CETP because of space and resource scarcity. So, these industries should be segregated from the residential neighborhoods and an environmentally sustainable community treatment plant for all of these industries should be designed comprehensively. It can be beneficial to reduce the pollution caused by these industries. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 89-105